Organelle contact sites : from molecular mechanism to disease - Tagaya, Mitsuo, 1958-; Simmen, Thomas (Springer, 2017)
"This book provides the first comprehensive coverage of the quickly evolving research field of membrane contact sites (MCS). A total of 16 chapters explain their organization and role and unveil the significance of MCS for various diseases. MCS, the intracellular structures where organellar membranes come in close contact with one another, mediate the exchange of proteins, lipids, and ions. Via these functions, MCS are critical for the survival and the growth of the cell. Owing to that central role in the functioning of cells, MCS dysfunctions lead to important defects of human physiology, influence viral and bacterial infection, and cause disease such as inflammation, type II diabetes, neurodegenerative disorders, and cancer. To approach such a multifaceted topic, this volume assembles a series of chapters dealing with the full array of research about MCS and their respective roles for diseases. Most chapters also introduce the history and the state of the art of MCS research, which will initiate discussion points for the respective types of MCS for years to come. This work will appeal to all cell biologists as well as researchers on diseases that are impacted by MCS dysfunction. Additionally, it will stimulate graduate students and postdocs who will energize, drive, and develop the research field in the near future"--Publisher's description.
Keywords: Cell membranes -- Metabolism.; Endoplasmic reticulum -- Metabolism.; Mitochondrial membranes -- Metabolism.; Cell interaction.; elektronické knihy; electronic books